2004
DOI: 10.1103/physrevb.70.085321
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of silicon surfaces: A stochastic optimization problem

Abstract: Over the last two decades, scanning tunnelling microscopy (STM) has become one of the most important ways to investigate the structure of crystal surfaces. STM has helped achieve remarkable successes in surface science such as finding the atomic structure of Si(111) and Si(001). For highindex Si surfaces the information about the local density of states obtained by scanning does not translate directly into knowledge about the positions of atoms at the surface. A commonly accepted strategy for identifying the a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
47
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 54 publications
5
47
0
Order By: Relevance
“…Our choice for developing this genetic algorithm (GA) was motivated by its successful application for the structural optimization of atomic clusters [11,12]. Like the previous study [10], the present algorithm also circumvents the intuitive process when proposing candidate models for a given high-index surface. Except for the periodic vectors of the surface unit cell [which can be determined from scanning tunnelling microscopy (STM) or from low-energy electron diffraction (LEED) measurements], no other experimental input is necessary.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Our choice for developing this genetic algorithm (GA) was motivated by its successful application for the structural optimization of atomic clusters [11,12]. Like the previous study [10], the present algorithm also circumvents the intuitive process when proposing candidate models for a given high-index surface. Except for the periodic vectors of the surface unit cell [which can be determined from scanning tunnelling microscopy (STM) or from low-energy electron diffraction (LEED) measurements], no other experimental input is necessary.…”
mentioning
confidence: 99%
“…However, the publication of numerous studies that report different structures for a given high-index silicon surface (see, e.g., [1,2,3,4,5]) indicates a need to develop methodologies capable of actually searching for the atomic structure in a way that does not predominantly rely on the heuristic reasoning associated with interpreting STM data. Recently, it was shown that parallel-tempering Monte Carlo (PTMC) simulations combined with an exponential cooling schedule can successfully address the problem of finding the reconstructions of high-index silicon surfaces [10]. The PTMC simulations, however, have a broader scope, as they are used to perform a thorough thermodynamic sampling of the surface systems under study.…”
mentioning
confidence: 99%
See 3 more Smart Citations